Peningkatan Hasil Belajar IPA Melalui Model Pembelajaran Quantum Teaching pada Peserta Didik Sekolah Dasar - Susy Ermawaty (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2024)
The learning model is one of the factors that determine the success of the learning process. Learning models that are not in accordance with the characteristics of students and learning materials can cause low learning outcomes. The purpose of the study was to improve learning outcomes on science learning material on the life cycle of living things through the use of the Quantum Teaching Learning Model. The research method used is Collaborative Classroom Action Research. The research subjects were fourth grade students of SD Negeri Keden 2 Kalijambe which amounted to 13 students. The research data was collected by using test technique using the instrument of description questions. The research data was analyzed descriptively quantitatively. Based on the research data, it is known that the learning outcomes of students have increased. Learners who get scores above the KKM for Pre-Cycle (15.38%), Cycle I (46.15%), and Cycle II (100%), so that the percentage increase in learning outcomes from Pre-Cycle to Cycle I is 30.77% and Cycle I to Cycle II is 53.85%. Thus, it can be concluded that the use of the Quantum Teaching learning model can improve student learning outcomes in science learning.